Bali Fusion Pop Music - I Wayan Sudirana (Journal of Music Science, Technology, and Industry, 2023)
Purpose: In this era of globalization, intercultural interaction between musicians from all over the world is inevitable. This worldwide interaction ultimately enriches contemporary music. Methods: As Blaukopf says, “acculturation doesn’t necessarily mean the loss of cultural identity; there is also acculturation which leads to enrichment in music, independent of its economical significance. Results and discussion: The emergence of fusion pop music groups is a response of the development of human’s culture. The commercialized forms of their musics are the effect of the rapid development of tourism industry in Bali. Their innovations and creative ideas are depending on their consumers’ needs. Implication: The positive outcome of these creative ideas is that composers are looking for new styles and ways of playing, composing, and exploring that do not intersect with traditional ones.